The formula of Islamic community development in Indonesia through the social entrepreneurship approach - Agus Ahmad Safei (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
This study aims to analyze the importance of a social entrepreneurship approach and celestial entrepreneurship in the midst of Islamic societies in Indonesia. Empirically, Indonesia as a country with the largest Muslim population in the world has great potential in developing community empowerment programs, especially in the Covid-19 pandemic situation which has created many new layers of indigent society. However, at the same time the availability of literature that examines social entrepreneurship as an important instrument of community development is relatively rare. Methodologically, this research is a library research conducted using literature in various forms, which are positioned equally depending on the connection with the main research topic. The results of this study indicate that developing a social entrepreneurship ecosystem that promotes innovation and collaboration is one of the solutions to overcome social problems that occur in the midst of the Indonesian Muslim community. In addition, this study also concludes that entrepreneurial practices carried out by the Muslim community are part of social responsibility, where the overall practice must be framed by Islamic values that prioritize the social dimension of humanity rather than being solely oriented to personal financial benefits.